Influence of P2O5 and Al2O3 content on the structure of erbium-doped borosilicate glasses and on their physical, thermal, optical and luminescence properties. (March 2015) - Bourhis, Kevin; Massera, Jonathan; Petit, Laeticia; Ihalainen, Heikki; Fargues, Alexandre; Cardinal, Thierry; Hupa, Leena; Hupa, Mikko; Dussauze, Marc; Rodriguez, Vincent; Boussard-Plédel, Catherine; Bureau, Bruno; et al.
Graphical abstract: Highlights: Reorganization of the glass structure induced by the addition of P2 O5 or Al2 O3 . Emission properties related to the presence of P or Al in the Er 3+ coordination shell. Declustering observed upon addition of P2 O5 . No declustering upon addition of Al2 O3 . Abstract: The effect of P2 O5 and/or Al2 O3 addition in Er-doped borosilicate glasses on the physical, thermal, optical, and luminescence properties is investigated. The changes in these glass properties are related to the glass structure modifications induced by the addition of P2 O5 and/or Al2 O3, which were probed by FTIR, 11 B MAS NMR and X-ray photoelectron spectroscopies. Variations of the polymerization degree of the silicate tetrahedra and modifications in the [3] B/ [4] B ratio are explained by a charge compensation mechanism due to the formation of AlO4, PO4 groups and the formation of AlOP linkages in the glass network. From the absorption and luminescence properties of the Er 3+ ions at 980 nm and 1530 nm, declustering is suspected for the highest P2 O5 concentrations while for the highest Al2 O3 concentrations no declustering is observed.